PENINGKATAN PROFESIONALISME GURU DAN KUALITAS PEMBELAJARAN BIOLOGI DI SEKOLAH MELALUI LESSON STUDY - Siti Sriyati (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2007)
This research was done to investigate impact of lesson study in order to improve teachers professionalism and the quality of teaching learning process in Biology. Although lesson study has been conducted since the year of 2005 at numerous schools in Bandung, information on how far such activity does give impact to teacher as instructoi and teacher as observer has not been covered. The research was undertaken by spreading questions to the instructor as well as the observer. Furthermore, qualityof teaching learning process in the school was observed at SMP Lab. School and SMA Lab. School UPI. The research resulted in insight that through lesson study, teachers both served as instructor and observer can improve such competency as pedagogy, professional, personality, social as clearly inclicated in